1994
DOI: 10.1159/000112127
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Central Nervous System: Monitoring the Metabolic Response using the Pentose Phosphate Pathway

Abstract: We propose that monitoring the activity of the pentose phosphate pathway (PPP) may provide an opportunity to obtain unique information regarding the metabolic response to oxidative stress since glutathione peroxidase activity is coupled, via glutathione reductase, to the PPP enzyme glucoses-phosphate dehydrogenase. PPP activity was quantitated from data obtained from gas chromatography/mass spectrometry analysis of released lactate following metabolic degradation of (1,6-13C2,6,6-2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 11 publications
5
45
0
1
Order By: Relevance
“…Nevertheless, astrocytes do not show signs of overt oxidative stress in our conditions, since neither an increase in the intracellular oxidized form of GSH, a change in the total intracellular GSH content, nor a loss of cellular viability could be observed. In contrast, these observations argue in favor of a cellular response mounted against pro-oxidative stimuli to provide sufficient NADPHreducing equivalents (Ben Yoseph et al, 1994;Rahman et al, 2000). Interestingly, we have recently described a similar mechanism following proinflammatory cytokines treatment of astrocytes (Gavillet et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, astrocytes do not show signs of overt oxidative stress in our conditions, since neither an increase in the intracellular oxidized form of GSH, a change in the total intracellular GSH content, nor a loss of cellular viability could be observed. In contrast, these observations argue in favor of a cellular response mounted against pro-oxidative stimuli to provide sufficient NADPHreducing equivalents (Ben Yoseph et al, 1994;Rahman et al, 2000). Interestingly, we have recently described a similar mechanism following proinflammatory cytokines treatment of astrocytes (Gavillet et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…PPP is essential for cell maintenance (2,4,10,24). The products of PPP, ribose-5-P (R5P), glyceraldehyde-3-P (G3P), and NADPH ϩ , are precursors for all deoxyribonucleotide triphosphates.…”
Section: Discussionmentioning
confidence: 99%
“…At least in cell culture experiments, it was demonstrated that astroglial cells protect neurons (Desagher et al, 1996;Langeveld et al, 1995) and oligodendrocytes (Noble et al, 1994) against H 2 O 2 toxicity. Neurons are more vulnerable against damaging compounds such as H 2 O 2 or peroxynitrite than cultured astroglial cells (Ben-Yoseph et al, 1994;Bolanos et al, 1995). One reason for this vulnerability might be that neurons in culture contain glutathione at a lower concentration than astroglial cells (Bolanos et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As in other cells and tissues, the pentose phosphate pathway (PPP) appears to be the predominant source in brain cells for generation of NADPH, which subsequently is necessary for the regeneration of GSH (Hotta, 1962;Hotta and Seventko, 1968). It was demonstrated in cell cultures that during the detoxification of H 2 O 2 , the PPP was more strongly activated in astroglial cells than in neurons (Ben-Yoseph et al, 1994) and, therefore, GPx appears to exert a key function in the detoxification of H 2 O 2 and peroxides by astroglial cells. At least for the detoxification of H 2 O 2 by cultured astroglial cells it has recently been demonstrated that glutathione is quickly oxidized after application of this compound and that both enzymes, GPx and catalase, are involved in the detoxification of H 2 O 2 by these cells .…”
Section: Introductionmentioning
confidence: 99%